The enjoyment of life in patients with Alzheimer’s disease: correlations with caregivers’ perceptions, caregiving attitudes, and empowerment levels - Jianhong Lv; Wenting Xu; Hongyan Mao; Fen Zhao; Wenxia Zhang; Jing Huang (BMC Nursing)
Abstract Aims This study aims to analyse the current state of life enjoyment among Alzheimer’s disease patients; and explore the correlations between life enjoyment of patients with Alzheimer’s disease and caregiver’s knowledge of Alzheimer’s disease, caregiving attitudes and caregiving empowerment. Design This research adopted a cross-sectional study approach. Methods A cross-sectional survey was conducted from May to August 2024. A convenience sampling method was employed to recruit 417 inpatients with Alzheimer’sdisease and their caregivers from tertiary-level hospitals, elderly healthcare facilities, and community welfare centres in Changsha, Hunan Province, China. The data collection tools included a general information questionnaire, the Pleasant Events Scale for Patients with Dementia (PES-AD), the Alzheimer’s Disease Knowledge Scale (ADKS), the Scale of Attitude Toward with Dementia (ATD) and the Empowerment Scale for Family Caregivers with Dementia (EFCD). The SPSS27.0 software was utilized to analyse the current state and influencing factors of the life enjoyment of patients with Alzheimer’s disease, and to investigate the correlations among caregivers’ caregiving attitudes, caregiving empowerment, knowledge level about the disease and patients’ life enjoyment. Results Patients with Alzheimer’s disease obtained scores of (17.33 ± 2.71) on the Pleasant Events Scale, (15.16 ± 2.99) on the Alzheimer’s Disease Knowledge Scale, (24.70 ± 1.21) on the Scale of Attitude Toward with Dementia, and (26.88 ± 1.65) on the Empowerment Scale for Family Caregivers with Dementia. The results of the Pearson’s correlation analysis indicated that there was a positive correlation between the Alzheimer’s disease pleasant events of patients and the knowledge, attitude, and empowerment of caregivers regarding Alzheimer’s disease (P < 0.05). The results of multiple linearregression analyses showed that patients’ gender, age, self-care situations, severity of diseases, caregiver’s cumulative duration of caregiving, the availability of shared caregivers, and whether caring for patients feels stress, whether or not educated about AD, knowledge of Alzheimer’s disease, caregiving attitudes, and caregiving empowerment were the main influences on patients’ sense of life enjoyment (P < 0.05). Conclusion The life pleasure of Alzheimer’s disease patients was at a medium level; caregivers’ knowledge of Alzheimer’s disease was at a medium level, while their caregiving attitude and caregiving empowerment were at a medium-high level. Future research can identify the most effective interventions based on caregivers’ knowledge of Alzheimer’s disease. This will facilitate the enhancement of disease-related health knowledge education and training, elevate caregivers’ awareness of the disease, and thereby improve the life pleasure of Alzheimer’s Disease (AD) patients. Impact At present, the caregiving issues for Alzheimer’s Disease Patients represents a global public health challenge, with caregiving capacity also significantly impacting patients’ quality of life. Thus, in order to decelerate AD progression and improve patients’ quality of life, a comprehensive analysis of caregivers’ Alzheimer’s Disease knowledge, caregiving attitudes, caregiving empowerment, and their correlation with patient outcomes is crucial for promoting the physical and mental health of AD patients in the future.